The Influence of the make a match model on Students’ Mapel PAI Learning Achivement and Civil Decision - Yusuf Ridho; Nur Hidayah; Lailla Hidayatul Amin (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to investigate the effect of using the Make a Match learning model in learning Islamic Religious Education and Character on the learning achievement of class VII students at State Junior High School 2 Tawangmangu. With a quantitative approach, this research involves a type of field research with an experimental design. Data was collected through direct observation in the field and the use of questionnaires to measure the level of implementation of the Make a Match model and student learning achievement. The research population was all class VII students with a total of 110 students, while the research sample was selected as 33 students using the random sample method. Data analysis was carried out using validity and reliability tests, as well as statistical analysis to determine the effect of using the Make a Match model on student learning achievement. The research results show that the level of use of the Make a Match model and student learning achievement are in the medium category. However, statistical analysis shows that there is no significant relationship between the use of the Make a Match model and student learning achievement. The correlation between the two variables is declared weak with a coefficient of 0.029 and a significance of 0.873. The conclusions of this research highlight the importance of further exploration of more effective learning methods in the context of religious and character education in junior high schools. This research provides insight into the effectiveness of the Make a Match learning model in the context of religious and character education at SMP Negeri 2 Tawangmangu. The implications of this research highlight the importance of further exploration of more effective and quality learning methods.